Bajo el signo de Napoleón. La Súplica constitucional de 1808 - Hespanha, António Manuel (Cuadernos de Historia Moderna, 2009)
Napoleonic presence in Portugal meant the first opportunity for a modern constitutionalism in that country. The instauration of a French-dependent government in Portugal, derived in a constitutional demand addressed to Napoleon in order to give to the (“amputated”) country a constitution like that of the Grand Duchy of Warsaw. This “Napoleonic constitution”, not very different from future Portuguese systems, represented a first model of conservative constitutional monarchy in Portugal, which involved: centralized executive, reformedoriented administration, political and social conservatism (but expressed by an ornamental revolutionary phraseology), a cult to the Nation State and the aspiration of a clear law and an efficient justice, both based on codification.